A brief historical review of Code Napoléon: A solemn understanding between revolution and tradition - Martin Rivera, Rafael (Derecho Público Iberoamericano, 2016)
Here is a small and humble contribution to the knowledge of part of this great historical, political and legal legacy, which has never been sufficiently acknowledged; one of the great "masses de granit" that were cast on French soil such that the scattered "grains de sable" of the Republic could be amalgamated, resulting in the founding of nations and testimony of European legal tradition. Two centuries after the Napoleon Code was enacted, it continues to be a magnificent and thought-provoking work for a number of reasons: its historical origins, its legal sources, its transnational influence and its permanence. But above a11 as a classical political synthesis between tradition ("traditio') and revolution and restoration ("revolutio et renovatio''); the result of the vital and intuitive genius of one of the great creators of European History: Napoleon Bonaparte